The Pedagogical Content Knowledge (PCK) of Prospective Teachers - Sutamrin Sutamrin; Rosidah Rosidah; Ahmad Zaki (PT ARRUS Intelektual Indonesia, 2022)
This research aims to find out the pedagogical content knowledge (PCK) of prospective teacher related to material at the junior high school level in terms of their academic abilities. To achieve the research target, 2 instruments were used, namely 1) a core instrument to measure emotional intelligence in the form of a questionnaire, 2) an interview guide related to the core instrument that had been filled in. This research was conducted at the Faculty of Mathematics and Natural Sciences, UNM Makassar in the Mathematics Department. Subjects were categorized into 2 categories, namely categories I and II based on their academic abilities as seen from the GPA of students while studying in the Mathematics Education Study Program. Prospective teacher students are given the core instrument to fill in, then 2 subjects in each category are selected for analysis of the results of filling in the core instrument and conducting interviews. The results of this study are that student teacher candidates 1) still lack orientation towards science teaching, 2) their knowledge of the curriculum still needs to be improved, 3) knowledge about understanding students' abilities still needs to be improved, 4) about science learning strategies still needs to be improved again and 5) still need to improve more knowledge in evaluating the learning process to identify misconceptions.